Personality and performance: moving beyond the Big 5. (August 2017) - Roberts, Ross; Woodman, Tim
Highlights: Personality is worthy of consideration in relation to performance. Research should go beyond the Big 5 to consider other relevant traits. The personality–performance relationship is best viewed through an interaction lens. Narcissists perform well under pressure but poorly when the pressure is off. Alexithymics' blunted emotional response likely aids performance under pressure. Abstract : In this review, we examine the literature in relation to personality and performance. Much of the extant work in this area has focused on the role of the Big 5 traits ( i.e., extraversion, conscientiousness, openness to experience, agreeableness, and neuroticism), at the expense of other personality variables that have a strong performance-focused rationale. Further, a focus on main effects has dominated the literature, without recourse to consider person × environment interactions. In this review we go beyond the Big 5 and consider the role of two personality traits, narcissism and alexithymia, in relation to performance. We demonstrate that both traits have considerable potential to explain differences in performance and that the personality–performance relationship is best viewed from an interactionist perspective. We close with a call for researchers to give more attention to personality in relation to performance.